Exact and Approximate Analytic Solutions of the Jeffery-Hamel Flow Problem by the Duan-Rach Modified Adomian Decomposition Method - Bougoffa, Lazhar; Mziou, Samy; Rach, Randolph C. (Mathematical modelling and analysis, 2016)
This paper aims to find the exact solution in an implicit form for the well-known nonlinear boundary value problem, namely the MHD Jeffery-Hamel problem, which can be described as the flow between two planes that meet at an angle. Also, two accurate approximate analytic solutions (series solution) are obtained by the variation of the power series method (VPS) and the Duan-Rach modified Adomian decomposition method (DRMA).